Competition for Leadership Promotes Contributions to Collective Action. (20th March 2018) - Harrell, Ashley
Abstract: Groups often designate a leader to enforce their members' contributions to collective efforts. Prior work has demonstrated that allowing groups to democratically elect a leader is particularly effective at enhancing cooperation once the elected leader obtains the position. Here I go further by considering whether people vie to win elected leadership positions, contributing more to collective efforts even before the leader is elected. Specifically, I demonstrate that groups typically elect their more cooperative members to leadership. Individual members anticipate this and compete for leadership by increasing their contributions to collective efforts when they expect leaders will be elected by voters with knowledge of candidates' prior behaviors, compared to when cooperative behaviors are visible, but leaders will be appointed (Study 1), or when leaders will be elected, but not on the basis of candidates' cooperative behaviors (Study 2). Though prior work has centered on the beneficial effects of elected leadership after an election is held, I demonstrate a novel mechanism by which elections promote cooperation: before the election is held, via competition for leadership. More generally, the results suggest that the leader selection process is a critical factor in determining the success of groups facing collective action problems.